2003
DOI: 10.1152/japplphysiol.00985.2002
|View full text |Cite
|
Sign up to set email alerts
|

Adult carotid chemoafferent responses to hypoxia after 1, 2, and 4 wk of postnatal hyperoxia

Abstract: Exposing newborn rats to postnatal hyperoxia (60% O2) for 1-4 wk attenuates the ventilatory and phrenic nerve responses to acute hypoxia in adult rats. The goal of this research was to increase our understanding of the carotid chemoreceptor afferent neural input in this depressed response with different durations of postnatal hyperoxic exposure. Rats were exposed from a few days before birth to 1, 2, or 4 wk of 60% O2 and studied after 3-5 mo in normoxia. The rats were anesthetized with urethane. Whole carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 16 publications
1
53
1
1
Order By: Relevance
“…Some of these soma are most likely from chemoafferent cells. Increased tissue levels of ROS within chemoafferent cell bodies may account for histologic evidence of cytotoxicity and ablation of hypoxic chemosensitivity in these cells, in newborn rats exposed to hyperoxia (10).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these soma are most likely from chemoafferent cells. Increased tissue levels of ROS within chemoafferent cell bodies may account for histologic evidence of cytotoxicity and ablation of hypoxic chemosensitivity in these cells, in newborn rats exposed to hyperoxia (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the presence of normoxia during the first 7-10 days of postnatal life in rats is critical for development of chemoreceptor sensitivity (1,2,7,15,29). Hypoxia causes injury to the developing brain (22,34,57) and could target structures involved in cardiovascular reflexes (4,13,32,49).…”
mentioning
confidence: 99%
“…Ling et al showed that the long-term facilitation of ventilatory responses is greater in 1-month-old rats than in 2-month-old rats [76]. And the initial 4 weeks of life are important for the maturation of the carotid body and chemoreflex responses, since previously exposure to hyperoxia throughout the period of 1-4 weeks of age result in an attenuation of the ventilatory and phrenic responses to acute hypoxia [77]. Reeves et al demonstrated that exposure to CIH during the first 30 days of life exhibited a decrease in the number of neurons that receiving vagal and glossopharyngeal projections in the NTS and nucleus ambiguus in accompany with an augmentation in the number of neurones receiving projections in the RVLM [78].…”
Section: The Role Of Nts and Rvlm In Cih Conditionmentioning
confidence: 99%